Broad-Spectrum Biosensor Capable of Detecting and Identifying Diverse Bacterial and Candida Species in Blood - Metzgar, David (American Society for Microbiology, 2013)
We describe an assay which uses broad-spectrum, conserved-site PCR paired with mass spectrometry analysis of amplicons (PCR/electrospray ionization-mass spectrometry [ESI-MS]) to detect and identify diverse bacterial and Candida species in uncultured specimens. The performance of the assay was characterized using whole-blood samples spiked with low titers of 64 bacterial species and 6 Candida species representing the breadth of coverage of the assay. The assay had an average limit of detection of 100 CFU of bacteria or Candida per milliliter of blood, and all species tested yielded limits of detection between 20 and 500 CFU per milliliter. Over 99% of all detections yielded correct identifications, whether they were obtained at concentrations well above the limit of detection or at the lowest detectable concentrations. This study demonstrates the ability of broad-spectrum PCR/ESI-MS assays to detect and identify diverse organisms in complex natural matrices that contain high levels of background DNA.